2018
DOI: 10.2319/111117-770.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reminder therapy for controlling bacterial plaque in patients undergoing orthodontic treatment: A systematic review and meta-analysis

Abstract: According to the existing high-quality evidence, reminder therapy is a valuable strategy and may contribute to the reduction of plaque and gingival indices as well as to the lower occurrence of white spots in patients subjected to orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
3
30
0
1
Order By: Relevance
“…The introduction of cellphone technology has had a tremendous effect on human lifestyle and the current results indicate that it could possibly be also incorporated in the orthodontist’s armamentarium against WSLs. This is in agreement with two previous reviews that also highlighted the possible benefit of active reminders in the fight against WSLs . This might be attributed to the well‐documented improvement in plaque accumulation and gingival score of patients in the active reminder group, since these are relevant to the WSLs’ pathogenetic mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…The introduction of cellphone technology has had a tremendous effect on human lifestyle and the current results indicate that it could possibly be also incorporated in the orthodontist’s armamentarium against WSLs. This is in agreement with two previous reviews that also highlighted the possible benefit of active reminders in the fight against WSLs . This might be attributed to the well‐documented improvement in plaque accumulation and gingival score of patients in the active reminder group, since these are relevant to the WSLs’ pathogenetic mechanism.…”
Section: Discussionsupporting
confidence: 92%
“…Current awareness of apps is poor, despite this finding, 87% of participants in this study reported that they would be willing to use an app to aid with treatment. A number of studies (Zotti et al 2015, Li et al 2016, Alkadhi et al 2017, Lima et al 2018 have shown apps to be effective in orthodontics, however, there are a number of limitations of apps. Given the availability of apps targeted at orthodontic patients, there is a need to assess the quality of these apps and if appropriate navigate patients towards high quality, effective apps.…”
Section: Resultsmentioning
confidence: 99%
“…Based on it, the use of mobile applications (apps) may be an important tool of communication between patients and professionals, besides providing the necessary instructions for the performance of exercises 14 . Reinforcing this hypothesis, a recent study 15 showed that reminder therapy is a valuable strategy and it may contribute to restore oral health. Other studies have also shown that reminder therapy is an effective strategy to increase follow‐up rate 16 and help the rehabilitation process after a stroke 17 .…”
Section: Introductionmentioning
confidence: 99%